Employee engagement: determinan dan dampaknya terhadap kinerja pegawai Ditjen Perbendaharaan di masa pandemi covid-19 - Dedi Supriadi; Aryana Satrya; Rini Yayuk Priyati (Direktorat Jenderal Perbendaharaan, Kementerian Keuangan, 2021)
The Coronavirus Disease 2019 (Covid-19) pandemic has presented its own challenges for public sector employees to achieve the best performance. The results of previous studies inform that work-life balance, supervisor support, and employee engagement can encourage employee performance improvement. This study aims to investigate how work-life balance and supervisor support can increase employee engagement which is the reason for improving public sector employee performance. To achieve this goal, research data was collected using an online survey to 257 employees of the Head Office of the Directorate General of Treasury. All of these data were processed and analyzed through the use of Structural Equation Modeling. The results showed that the effect of work-life balance and supervisor support was directly and significantly to encourage employee performance and employee engagement. In addition, it is also known that employee engagement is able to play its role as a mediating variable that strengthens the effect of work-life balance and supervisor support on employee performance.